Ecological and control techniques for sand flies (Diptera: Psychodidae) associated with rodent reservoirs of leishmaniasis. - Thomas M Mascari; Hanafi A Hanafi; Ryan E Jackson; Souâd Ouahabi; Btissam Ameur; Chafika Faraj; Peter J Obenauer; Joseph W Diclaro; Lane D Foil (Public Library of Science (PLoS), 2013)
BACKGROUND: Leishmaniasis remains a global health problem because of the substantial holes that remain in our understanding of sand fly ecology and the failure of traditional vector control methods. The specific larval food source is unknown for all but a few sand fly species, and this is particularly true for the vectors of Leishmania parasites. We provide methods and materials that could be used to understand, and ultimately break, the transmission cycle of zoonotic cutaneous leishmaniasis. METHODS AND FINDINGS: We demonstrated in laboratory studies that analysis of the stable carbon and nitrogen isotopes found naturally in plant and animal tissues was highly effective for linking adult sand flies with their larval diet, without having to locate or capture the sand fly larvae themselves. In a field trial, we also demonstrated using this technique that half of captured adult sand flies had fed as larvae on rodent feces. Through the identification of rodent feces as a sand fly larval habitat, we now know that rodent baits containing insecticides that have been shown in previous studies to pass into the rodents' feces and kill sand fly larvae also could play a future role in sand fly control. In a second study we showed that rubidium incorporated into rodent baits could be used to demonstrate the level of bloodfeeding by sand flies on baited rodents, and that the elimination of sand flies that feed on rodents can be achieved using baits containing an insecticide that circulates in the blood of baited rodents. CONCLUSIONS: Combined, the techniques described could help to identify larval food sources of other important vectors of the protozoa that cause visceral or dermal leishmaniasis. Unveiling aspects of the life cycles of sand flies that could be targeted with insecticides would guide future sand fly control programs for prevention of leishmaniasis.